Certain Oberhettinger2019;s Integrals Associated with Product of General Polynomials and Incomplete H- Function (Global Journal of Science Frontier Research, 2022)
In this paper we developed Oberhettinger s integral formulas containing the product of general polynomials and incomplete H-functions These integral formulas are very useful to obtain the Mellin transform of various simpler special functions The Mellin transform of special functions find their applications in mathematical statistics number theory and the theory of asymptotic expansions The main findings of the present work are very useful in solving the problems arising in digital signals image processing finance and ship target recognition by sonar system and radar signals
Keywords: incomplete H-functions; gamma functions; improper integrals; general polynomials